2014
DOI: 10.3748/wjg.v20.i3.714
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-associated immune thrombocytopenia: Clinical features and pathogenic mechanisms

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease mediated by anti-platelet autoantibodies. There is growing evidence that the eradication of Helicobacter pylori (H. pylori) effectively increases platelet count in a considerable proportion of ITP patients infected with this bacterium. In the majority of ITP patients responding to H. pylori eradication therapy, the anti-platelet autoantibody response is completely resolved with no relapse for more than 7 years, indicating that the disease is cured. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 71 publications
0
78
1
5
Order By: Relevance
“…As most of the studies included in the meta-analysis by Stasi et al [29] considered H. pylori eradication in primarily severe cases of ITP, absolute patient response rates to bacterial eradication treatment may exceed 50% efficacy. In patients that respond to H. pylori eradication therapy, autoplatelet Ab responses are completely resolved, without relapse for over 7 years [95]. However, platelet response to H. pylori eradication for the treatment of ITP appears to correlate with geographic location: higher response rates are observed in Japan and Italy (ranging from 28 to 100%) than in the United States and other European countries (<13%) [95].…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…As most of the studies included in the meta-analysis by Stasi et al [29] considered H. pylori eradication in primarily severe cases of ITP, absolute patient response rates to bacterial eradication treatment may exceed 50% efficacy. In patients that respond to H. pylori eradication therapy, autoplatelet Ab responses are completely resolved, without relapse for over 7 years [95]. However, platelet response to H. pylori eradication for the treatment of ITP appears to correlate with geographic location: higher response rates are observed in Japan and Italy (ranging from 28 to 100%) than in the United States and other European countries (<13%) [95].…”
Section: Clinical Relevancementioning
confidence: 99%
“…In patients that respond to H. pylori eradication therapy, autoplatelet Ab responses are completely resolved, without relapse for over 7 years [95]. However, platelet response to H. pylori eradication for the treatment of ITP appears to correlate with geographic location: higher response rates are observed in Japan and Italy (ranging from 28 to 100%) than in the United States and other European countries (<13%) [95]. A study from Iran reported that H. pylori eradication led to increased platelet count in those with mild ITP (platelet count >50 × 10 3 μL), but was less successful in patients with severe ITP (platelet count <50 × 10 3 μL) [96].…”
Section: Clinical Relevancementioning
confidence: 99%
“…It usually resolves spontaneously within 6 months of diagnosis. However, approximately 20% of newly diagnosed children with ITP progress to a chronic form, defined as persistence of thrombocytopenia for more than 12 months [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a diminished peripheral platelet count (< 100 × 10 9 /L) caused by platelet destruction with an increased risk of mucocutaneous bleeding [1]. It is usually a benign, self-limiting disease in children [2].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis is unknown but may involve the development of cross reactive antibodies to H. pylori and platelet antigens. [15] H. pylori infection activates monocyte/macrophage function which increases platelet removal. Also, H. pylori infection causes a non-specific stimulation of the immune system which may lead to platelet removal.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%